2000
DOI: 10.1159/000053256
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Sex and Age at Onset on Autoantibodies against Insulin, GAD<sub>65</sub> and IA2 in Recent Onset Type 1 Diabetic Patients

Abstract: Methods: Autoantibodies against insulin (IAA), glutamic acid decarboxylase (GADA) and tyrosine phosphatase IA2 (IA2A) were measured in sera from 448 recent onset patients with type 1 diabetes mellitus (DM) subdivided according to sex (194 female and 254 male) and age at onset (134 patients diagnosed before 10 years, 187 between 10 and 20 years, 66 between 20 and 30 years and 61 over 30 years. Results: Autoantibodies were more frequent in female DM patients (93.8 vs. 86.6%, p = 0.013) due to an increased preval… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
11
5

Year Published

2003
2003
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 19 publications
5
11
5
Order By: Relevance
“…It has been shown that GADA and IAA in recent onset T1D patients were more frequent among female (25), similarly our findings support that IAA titers were higher in females compared to males (p=0.026, r=0.26). The same study demonstrated higher GADA titers in older patients as shown in our study (p<0.001, r=0.502).…”
Section: Discussionsupporting
confidence: 89%
“…It has been shown that GADA and IAA in recent onset T1D patients were more frequent among female (25), similarly our findings support that IAA titers were higher in females compared to males (p=0.026, r=0.26). The same study demonstrated higher GADA titers in older patients as shown in our study (p<0.001, r=0.502).…”
Section: Discussionsupporting
confidence: 89%
“…Diagnosis of the disease was done according to the World Health Organization (WHO) criteria [17]. All patients with type 1 diabetes (average onset age 8.8 ± 3.9 years) were positive for one or more of the measured pancreatic autoantibodies (IAA, GADA and IA2A) determined in serum at diagnosis, using previously described standardized radio-assays [1]. …”
Section: Methodsmentioning
confidence: 99%
“…In this disorder, glutamic acid decarboxylase (GADA), tyrosine phosphatase (IA2A), zinc transporter 8 (ZnT8A) and insulin autoantibodies (IAA) are currently recognized as autoimmune process markers [1, 2]. The pathogenesis of the disease is determined by complex interactions between several genetic loci and environmental factors.…”
Section: Introductionmentioning
confidence: 99%
“…GADA and IA2A were detected using standard radiobinding assays with [ 35 S]‐labelled recombinant human GAD 65 and IA2 antigens obtained by in vitro translation using cDNA clones kindly provided by Dr Å. Lernmark (University of Washington, Seattle, WA, USA) and Dr E. Bonifacio (Istituto Scientifico San Raffaele, University of Milan, Italy), respectively . Cruces Hospital Laboratory participated in different Immunology of Diabetes Workshop (IDW) Proficiency Tests, generally obtaining 100% sensitivity and specificity for all three antibody assays .…”
Section: Methodsmentioning
confidence: 99%